2018
DOI: 10.3389/fenrg.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Improved Enzymatic Hydrolysis of Pilot Scale Pretreated Rice Straw at High Total Solids Loading

Abstract: Enzymatic hydrolysis at high solids loading has the potential to reduce both capital and operational expenditures. Here, pretreatment of rice straw (PRS) with dilute acid was carried out at a pilot scale (250 kg per day) at 162 • C for 10 min and 0.35% acid concentration, followed by enzymatic hydrolysis at different total solids loadings. It showed that although the total sugar concentration increased from 48 to 132 g/l, glucan conversion reduced by 27% (84-66.2%) with increasing solids from 5 to 20% in batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 51 publications
1
17
1
1
Order By: Relevance
“…through a reduction in the enzyme dosage required for achieving similar cellulose conversion on pretreated spruce, where 6 g/100 g red saponin dosage combined with 7.5 FPU/g cellulase loading gave a conversion comparable to that achieved by using 4 g/100 g saponins and 10 FPU/g. (A) (B) The concentrations of glucose obtained in this study are higher than those achieved by Nogueira et al [42] and Li [43] using PEG4000 as surfactant; however, the values are lower compared with the studies reported by Vignesh et al [42] and Agrawal et al [44]. Some of the works reported in Table 6 used high solid pretreated loading in the enzymatic hydrolysis process (20-35%, w/v); therefore, the operation of high solid loading is an important operative strategy that together with the use of surfactants can overcome the development of second-generation biorefineries producing high concentrations of fermentable sugars.…”
Section: Enzyme Loading Evaluationcontrasting
confidence: 69%
“…through a reduction in the enzyme dosage required for achieving similar cellulose conversion on pretreated spruce, where 6 g/100 g red saponin dosage combined with 7.5 FPU/g cellulase loading gave a conversion comparable to that achieved by using 4 g/100 g saponins and 10 FPU/g. (A) (B) The concentrations of glucose obtained in this study are higher than those achieved by Nogueira et al [42] and Li [43] using PEG4000 as surfactant; however, the values are lower compared with the studies reported by Vignesh et al [42] and Agrawal et al [44]. Some of the works reported in Table 6 used high solid pretreated loading in the enzymatic hydrolysis process (20-35%, w/v); therefore, the operation of high solid loading is an important operative strategy that together with the use of surfactants can overcome the development of second-generation biorefineries producing high concentrations of fermentable sugars.…”
Section: Enzyme Loading Evaluationcontrasting
confidence: 69%
“…The VS content is an indicator of the biodegradability of the samples and represents the portion of substrate that can be converted into biogas and biomethane. Research has shown that high VS content is a desirable condition in the anaerobic digestion process since it leads to higher biogas and biomethane yields [51,52].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Concerning the TS composition, in both fractions (solid and liquid), the samples taken from the hydrolysis step had the highest levels of TS content, probably due to the added enzyme which works as a catalyst, improving hydrolysis efficiency and leading to higher TS contents [20]. In almost all situations, samples from the pretreatment stage had the lowest TS values.…”
Section: Chemical Compositionmentioning
confidence: 99%